Neoadjuvant FOLFIRINOX in Patients With Borderline Resectable Pancreatic Cancer: A Systematic Review and Patient-Level Meta-Analysis. (14th May 2019) - Janssen, Quisette P; Buettner, Stefan; Suker, Mustafa; Beumer, Berend R; Addeo, Pietro; Bachellier, Philippe; Bahary, Nathan; Bekaii-Saab, Tanios; Bali, Maria A; Besselink, Marc G; Boone, Brian A; Chau, Ian; et al.
Abstract: Background: FOLFIRINOX is a standard treatment for metastatic pancreatic cancer patients. The effectiveness of neoadjuvant FOLFIRINOX in patients with borderline resectable pancreatic cancer (BRPC) remains debated. Methods: We performed a systematic review and patient-level meta-analysis on neoadjuvant FOLFIRINOX in patients with BRPC. Studies with BRPC patients who received FOLFIRINOX as first-line neoadjuvant treatment were included. The primary endpoint was overall survival (OS), and secondary endpoints were progression-free survival, resection rate, R0 resection rate, and grade III–IV adverse events. Patient-level survival outcomes were obtained from authors of the included studies and analyzed using the Kaplan-Meier method. Results: We included 24 studies (8 prospective, 16 retrospective), comprising 313 (38.1%) BRPC patients treated with FOLFIRINOX. Most studies (n = 20) presented intention-to-treat results. The median number of administered neoadjuvant FOLFIRINOX cycles ranged from 4 to 9. The resection rate was 67.8% (95% confidence interval [CI] = 60.1% to 74.6%), and the R0-resection rate was 83.9% (95% CI = 76.8% to 89.1%). The median OS varied from 11.0 to 34.2 months across studies. Patient-level survival data were obtained for 20 studies representing 283 BRPC patients. The patient-level median OS was 22.2 months (95% CI = 18.8 to 25.6 months), and patient-level median progression-free survival was 18.0 months (95% CI = 14.5 to 21.5 months). Pooled event rates for grade III–IV adverse events were highest for neutropenia (17.5 per 100 patients, 95% CI = 10.3% to 28.3%), diarrhea (11.1 per 100 patients, 95% CI = 8.6 to 14.3), and fatigue (10.8 per 100 patients, 95% CI = 8.1 to 14.2). No deaths were attributed to FOLFIRINOX. Conclusions: This patient-level meta-analysis of BRPC patients treated with neoadjuvant FOLFIRINOX showed a favorable median OS, resection rate, and R0-resection rate. These results need to be assessed in a randomized trial.